2011
DOI: 10.1364/ao.50.001995
|View full text |Cite
|
Sign up to set email alerts
|

All-optical analog-to-digital conversion scheme based on Sagnac loop and balanced receivers

Abstract: An all-optical analog-to-digital conversion scheme based on a Sagnac loop and balanced receivers is proposed and experimentally demonstrated. Adjustable phase shift about the transfer function of the Sagnac loop is obtained by using the multiwavelength optical pulses to realize the phase-shift optical quantization. Benefit from the complementary outputs at the transmitted and reflected ports of the Sagnac loop and balanced receiver can be used to obtain the quantized output binary signal for the encoding opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…[1][2][3] The electrical ADC whose sample rate is only several gage-samples per second (GSa∕s) cannot meet the requirements of ultrawide-band applications because of its inherent electrical bottle-neck such as clock jitter and sampling aperture. [1][2][3][4] Optical signal processing has attracted researchers' interests because it can overcome the electrical limitations. [5][6][7][8] Bres et al 9 demonstrated a 320 Gb∕s optical demultiplexing sampling method that required a mode-locked laser with a very high repetition rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The electrical ADC whose sample rate is only several gage-samples per second (GSa∕s) cannot meet the requirements of ultrawide-band applications because of its inherent electrical bottle-neck such as clock jitter and sampling aperture. [1][2][3][4] Optical signal processing has attracted researchers' interests because it can overcome the electrical limitations. [5][6][7][8] Bres et al 9 demonstrated a 320 Gb∕s optical demultiplexing sampling method that required a mode-locked laser with a very high repetition rate.…”
Section: Introductionmentioning
confidence: 99%
“…Analog-to-digital convertor (ADC) as a very important component in communication system needs to satisfy the requirements of the rapid development of ultrawide-band applications such as advanced radar communication system, high-speed optical communication, and so on [1][2][3]. The electrical ADC whose sample rate and quantization resolution are several giga-samples per second (GSa/s) and 10 bit, respectively, cannot satisfy the requirements of ultrawide-band applications, because of its inherent electrical bottleneck such as clock jitter and sampling aperture [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical ADC whose sample rate and quantization resolution are several giga-samples per second (GSa/s) and 10 bit, respectively, cannot satisfy the requirements of ultrawide-band applications, because of its inherent electrical bottleneck such as clock jitter and sampling aperture [1][2][3][4]. All-optical ADC has attracted much attention because it can cope with the problems in the electrical field, as well as achieves appropriate resolution and sampling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive optical quantization schemes have been proposed and improved aiming to achieve high quantization resolution, e.g. the phase quantization by the modulation and interference [7][8][9][10][11][12][13][14][15] and the frequency quantization by the nonlinear effects in highly nonlinear fibers [16][17][18][19][20][21]. In these schemes, the cascade quantization methods demonstrated in [12] and [13] have great advantages compared to the other schemes because the enhancement of more than 1-bit in the quantization resolution can be obtained on the basis of the conventional phase quantization schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The first-stage quantization module implements the N-channel phase-shifted optical quantization (PSOQ) and provides N different sinusoidal power transfer functions corresponding to the different channels. When it is directly followed by the photo detection and binary decision, the PSOQ module provides the number of bits (NOB) of log 2 (2N)-bit [7,8]. The inset (a) of Fig.…”
Section: Introductionmentioning
confidence: 99%